2005
DOI: 10.1037/0022-3514.88.3.547
|View full text |Cite
|
Sign up to set email alerts
|

Universal Features of Personality Traits From the Observer's Perspective: Data From 50 Cultures.

Abstract: To test hypotheses about the universality of personality traits, college students in 50 cultures identified an adult or college-age man or woman whom they knew well and rated the 11,985 targets using the third-person version of the Revised NEO Personality Inventory. Factor analyses within cultures showed that the normative American self-report structure was clearly replicated in most cultures, and was recognizable in all. Sex differences replicated earlier selfreport results, with the most pronounced differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

52
849
7
23

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,097 publications
(931 citation statements)
references
References 37 publications
52
849
7
23
Order By: Relevance
“…First, the present results are based primarily on self-report. McCrae et al (2005) replicated patterns of trait differences in observer reports of young adults. A similar replication in older adults is required to rule out reporting bias.…”
Section: Discussionmentioning
confidence: 66%
“…First, the present results are based primarily on self-report. McCrae et al (2005) replicated patterns of trait differences in observer reports of young adults. A similar replication in older adults is required to rule out reporting bias.…”
Section: Discussionmentioning
confidence: 66%
“…This might be attributed to the heterogeneity of PDs' symptoms. 1,2 Interestingly, the cross-cultural differences for internal reliabilities were rather small for the IPDE and larger for the NEO-PI-R. For the NEO-PI-R, lower internal reliabilities were already reported for several non-Western cultures, 19,21 and could be attributed to differences in response styles. However, Rossier and colleagues suggested that "in collectivistic cultures, behavior is determined more by social context than by traits and thus behaviors-and response to questionnaire items-do not reflect the consistent operation of traits."…”
Section: Discussionmentioning
confidence: 96%
“…Recently, Rossier and colleagues 18 extended these results from Asian and Western cultures to Africa by analyzing the NEO-PI-R factor structure in Burkina Faso, which was very similar to the American normative structure, with a total congruence coefficient of 0.94. Recently, McCrae and colleagues 19 analyzed the replicability of the FFM personality structure using observer-rating personality data from 50 cultures representing 6 of the 7 continents. Factor analyses within cultures showed that the FFM personality structure replicated in most cultures and was recognizable in all.…”
mentioning
confidence: 99%
“…Por outro lado, quando se parte de traduções de instrumentos do inglês e adapta-se para outras culturas (etic studies), os resultados são mais promissores em apontar para a estrutura penta-fatorial (McCrae et al, 2005). Hutz et al (1998), por exemplo, inspiraram-se nos marcadores de Goldberg (1992) e Norman (1963), em inglês, e em seus próprios levantamentos com universitários para desenvolver uma lista de adjetivos descritores de personalidade em português do Brasil.…”
unclassified